Facile synthesis of MoS2 quantum dots as fluorescent probes for sensing of hydroquinone and bioimaging. Issue 26 (25th June 2019) - Li, Lu; Guo, Zhihua; Wang, Shengxu; Li, Daowei; Hou, Xianfeng; Wang, Fangting; Yang, Yizhou; Yang, Xudong
Abstract : A simple, low-cost and one-step hydrothermal treatment for the synthesis of molybdenum disulfide quantum dots (MoS2 QDs) is proposed. They exhibit excellent PL properties and can be promising probes for sensing of hydroquinone and bioimaging. Abstract : Recently, transition metal dichalcogenide quantum dots have attracted widespread attention among researchers as fluorescent materials. In this work, a facile bottom–up route is proposed to synthesize water-soluble molybdenum disulfide quantum dots (MoS2 QDs) by using sodium molybdate and cysteine as precursors. The as-prepared spherical MoS2 QDs with an average size of 3.5 nm exhibit intense PL emission, whose quantum yield (QY) is 6.5% (cal.). In particular, the as-synthesized MoS2 QDs show highly sensitive and selective detection of H2 Q. The lowest limit of detection can reach 0.3 μM in water, far lower than the estimated wastewater discharge limit of the United States Environmental Protection Agency (EPA) (0.5 mg L −1 ). What is more, the as-prepared MoS2 QDs exhibited applicability in cell imaging with lower cytotoxicity. Therefore, the as-prepared MoS2 QDs show potential applications in environmental monitoring, bioanalysis, disease diagnosis and treatment, etc.